2013
DOI: 10.1155/2013/196012
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Inflammatory Bowel Disease with Cytoplasmic Staining of Antineutrophil Cytoplasmic Antibodies

Abstract: Background. It is unusual for the antineutrophil cytoplasmic antibody with cytoplasmic pattern (cANCA) to present in patients with inflammatory bowel disease (IBD) without vasculitis. The purpose of this study was to describe the occurrence and characteristics of pediatrics IBD with cANCA. Methods. A retrospective review of pediatric IBD associated with cANCA serology in patients from King Abdulaziz University Hospital, Saudi Arabia, between September 2002 and February 2012. Results. Out of 131 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…In our present study, we identified the prevalence of p-ANCA as 22.2% in patients with UC, which was similar to that in a Korean report (22.1%) but was lower than that in a report from China (43.4%) [42, 43]. Moreover, we also identified that the prevalence of c-ANCA was 1.6% in patients with UC, which was lower than that in previous reports from Jeddah (3%), Japan (39.2%), and England (31%) [4446].…”
Section: Discussionsupporting
confidence: 73%
“…In our present study, we identified the prevalence of p-ANCA as 22.2% in patients with UC, which was similar to that in a Korean report (22.1%) but was lower than that in a report from China (43.4%) [42, 43]. Moreover, we also identified that the prevalence of c-ANCA was 1.6% in patients with UC, which was lower than that in previous reports from Jeddah (3%), Japan (39.2%), and England (31%) [4446].…”
Section: Discussionsupporting
confidence: 73%
“…Another study suggests that an ethnic basis (Indian origin) may influence the tendency to the response by synthesis of anti-PR3 in UC patients. These IBD pediatric patients with the rare association of PR3 antibodies did not show any evidence of systemic or local vasculitis [ 26 ]. It is obvious that the target antigen has not yet been fully identified and the development of new sensitive methods can yield new insights into this issue.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Proteinase 3 (PR3), which is a serine protease in azurophilic granules, is an antigen of c-ANCAs. Saadah and Al-Mughales 15 showed that c-ANCAs were positive in only 5.3% of IBD patients (7/131) and were not specific for UC (4 UC and 3 CD). Despite the fact that few reports have described an association between c-ANCAs and IBD, Arias-Loste et al 16 and Mahler et al 17 were the first to demonstrate that PR3-ANCA measurement is useful for the diagnosis of UC.…”
Section: Introductionmentioning
confidence: 99%